Diagnosis and Surgical Management of Annular Pancreas in an 18-Day-Old Neonate: A Case Report - Alim, Tasya Fabiola; Alim, Linawati; Alim, Kenny Dion (Medicinus, 2024)
Background: This case report presents a rare and challenging condition—annular pancreas—in an 18-day-old neonate. Annular pancreas is a congenital anomaly where a ring of pancreatic tissue encircles the duodenum, leading to gastrointestinal obstruction. Early diagnosis and intervention are crucial for optimal patient outcomes. The rarity of this condition in neonates underscores its clinical significance. Case Description: The patient presented with a history of persistent vomiting since birth, which initially appeared green but later turned yellow. The infant had been fed various types of milk sequentially, with vomiting occurring after each feeding. Additionally, the infant developed jaundice a week prior to presentation, which was treated without improvement in symptoms. Diagnostic modalities included abdominal X-ray, ultrasound, and upper gastrointestinal contrast study, which collectively confirmed a partial obstruction at the gastroduodenal junction due to annular pancreas. The definitive treatment involved a laparotomy for exploratory surgery, followed by a duodenoduodenostomy using the Kimura technique to address the anatomical abnormality. Postoperative management included prophylactic antibiotics, anti-emetic therapy, acid suppression, and probiotics to support recovery. The outcome of the case was favorable, with successful resolution of the gastrointestinal obstruction following the surgical intervention. Conclusions: This case underscores the importance of early recognition, precise diagnosis, and multidisciplinary intervention in managing congenital anomalies like annular pancreas, ultimately leading to favorable outcomes and improved quality of life for neonatal patients..